2020
DOI: 10.3390/ijms22010001
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Protein Network: From Biogenesis to Bioenergetics in Health and Disease

Abstract: Mitochondria are double membrane-bound organelles which are essential for the viability of eukaryotic cells, because they play a crucial role in bioenergetics, metabolism and signaling [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Numerous studies conducted over the years have provided evidence that mitochondrial dysfunction serves as the underlying cause in the development of neurodegenerative diseases, which include Alzheimer's disease (AD), Parkinson's disease (PD), Huntington's disease (HD), Amyotrophic Lateral Sclerosis (ALS) and Dementia [26][27][28][29]. These diseases arise from deficiencies in mitochondrial function, which is primarily regulated by over 1000 proteins encoded by both the mitochondrial and nuclear genomes [30]. Studies have shown that the majority, around 90%, of mitochondrial proteins are encoded by genes found in the cell nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies conducted over the years have provided evidence that mitochondrial dysfunction serves as the underlying cause in the development of neurodegenerative diseases, which include Alzheimer's disease (AD), Parkinson's disease (PD), Huntington's disease (HD), Amyotrophic Lateral Sclerosis (ALS) and Dementia [26][27][28][29]. These diseases arise from deficiencies in mitochondrial function, which is primarily regulated by over 1000 proteins encoded by both the mitochondrial and nuclear genomes [30]. Studies have shown that the majority, around 90%, of mitochondrial proteins are encoded by genes found in the cell nucleus.…”
Section: Introductionmentioning
confidence: 99%